Comparative study of a standard game situation in the African and European Football championships 2004 - Algol, Kamal (2006)
It was analyzed totally 1150 standard situations (direct, corner, penalty, and indirect) at the European and African football championships 2004. The result was compare it. Between the European and African championships were no significant statistical differences in successful and unsuccessful free kicks. The most scored goals from the free kicks were at last 15 minute in most matches of both championships. The most scored goals from the free kicks were from the distance between 16-25 meters. The foot internal face was the most effectiveness for scoring the goal. Percentage goals of free kicks from the all goals were 46.39% in Europe championship and 33.33% in African championship.